Les inégalités d’accès dans l’enseignement supérieur français depuis 1998 : beaucoup de réformes pour des résultats mitigés. - Magali Jaoul-Grammare (Éducation et Socialisation)
The French higher education system is characterized by a dual system -universities and “elite schools”- which is at the root of many inequalities that politics try to fight against. Since the 1980s, equal opportunities were at the heart of all educational reforms and the fight against inequalities became the priority whether they are gendered, geographical, social or cultural. Starting from this point, the aim of this work is to analyze the effects of the various reforms on the evolution of the inequalities of access to higher education especially with regard to prestigious courses. We use a multinomial logistic regression to compare the Cereq database Generation 1998 and 2013 focusing on four vectors of inequalities: gender, social, cultural and geographical inequalities. Our results show that in spite of a reduction of some inequalities, access to various areas of higher education and more particularly access to prestigious and selective training courses, remains affected by inequalities, in particular by gender and social inequalities.